In vitro study of the anticoagulant efficacy of lemon verbena and lemongrass extracts - حسن نعمى (Latakia University Journal -Medical Sciences Series, 2024)
Aloysia citrodora or Lemon verbena is a plant rich in phenolic compounds, and exhibits lots of medical properties, such as antioxidant, antimicrobial, sedative, narcotic and anxiolytic properties. Andropogon citrates or Lemongrass is used as a traditional remedy in folk medicine to treat many diseases such as digestive disorders, cough, and others. It is known for its antioxidant, anti-inflammatory, antibacterial and antifungal effects, due to its content of phenolic compounds. The anticoagulant effect of the two mentioned plants has not yet been studied, although phenols have a known anticoagulant activity. This study aimed to investigate the in vitro anticoagulant activity of aqueous extracts of Lemon verbena and Lemongrass by testing their effect on prothrombin time using plasma from healthy individuals and comparing the efficacy of both plants. Aqueous extracts of the two plants were prepared and the total phenolic content TPC was determined. The TPC in lemon verbena extract was 10.825 g GAE /L and 8.235 g GAE /L in lemongrass extract. Different concentrations were prepared to investigate their effect on prothrombin time. The studied concentrations of lemon verbena showed a significant increase in prothrombin time compared to distilled water and the effect was concentration dependent. Also, the increasing concentrations of lemongrass showed an increase in PT but the difference was not significant at all studied points. The results indicate that the two extracts have anticoagulant activity in vitro due to their content of phenolic compounds with a superior effect of lemon verbena.